«Green» practices of Kharkiv residents during the war: results of Kharkiv Green Urban Tour 2023 - Zaporozhchenko Ruslan; Shymansky Denys (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2023)
The article is devoted to revealing the «green» practices of Kharkiv residents during the war, namely the continuation of growing home-grown vegetables and fruits and their distribution in the context of urban farming. After all, on February 24, 2022, when Russia`s full-scale military invasion of Ukraine began, urbanized Kharkiv was on the verge of a humanitarian catastrophe: logistics routes for the delivery of food and goods were damaged, infrastructure and residential areas were constantly shelled, and a huge number of people were forced to leave the city and move to safer regions of Ukraine. These factors demonstrated new challenges, new threats, and new trends that the city’s remaining residents had to face and adapt to. In this article, we will focus on the results of the Kharkiv Green Urban Tour 2023, which was held in April-May 2023 and aimed to communicate with residents of different districts of Kharkiv about urban farming, gardening, and green practices. This initiative was carried out as part of the international research project FUSILLI (Fostering the Urban Food System Transformation through Innovative Living Labs Implementation) at the School of Sociology of V.N. Karazin Kharkiv National University, funded by the European Union`s Horizon 2020 Research and Innovation Program under the grant agreement No.101000717. The results of this study will provide us with a clearer understanding of how and in what ways residents of an urbanized city engage in improvised farming, gardening, growing vegetables, adapting to the military situation, and reproducing “green” practices while helping others.